Onshore structural design calculations power plant and energy processing facilities - El-Reedy, Mohamed A. (Mohamed Abdallah) (Butterworth-Heinemann, 2017)
Onshore Structural Design Calculations: Energy Processing Facilities provides structural engineers and designers with the necessary calculations and advanced computer software program instruction for creating effective design solutions using structural steel and concrete, also helping users comply with the myriad of international codes and standards for designing structures that is required to house or transport the material being processed. In addition, the book includes the design, construction, and installation of structural systems, such as distillation towers, heaters, compressors, pumps, fans, and building structures, as well as pipe racks and mechanical and electrical equipment platform structures. Each calculation is discussed in a concise, easy-to-understand manner that provides an authoritative guide for selecting the right formula and solving even the most difficult design calculation.--Provided by publisher.